PENYELESAIAN HUKUM TERHADAP FRANCHISOR MENUTUP WARALABA SECARA SEPIHAK DALAM PERJANJIAN WARALABA - Priscilla, Putu Meidina; Putra, Made Aditya (Kertha Negara : Journal Ilmu Hukum, 2024)
Franchising is one of the fastest growing business innovations and is considered low risk. A franchise or franchise business involves two parties: the franchise as the buyer of the business brand and his franchisor as the owner and seller of the business brand. A franchise or franchise business requires a franchise agreement as a license to use intellectual property rights for the business. A franchise or franchise agreement may also be subject to disputes between the parties. An example of a dispute is when a franchisor unilaterally terminates a contract before it expires, causing a loss to the franchise. The question raised in this study concerns the legal protections afforded to franchisees and franchisors in the event of default. Also legal restrictions in case of unilateral de-franchising by the franchisor. This study is a normative legal study. This research examines laws and regulations as the main sources of information: the Civil Code, Government Regulation of the Republic of Indonesia No. 42 of 2007 on Franchises, and Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution. In addition, we utilize secondary and tertiary sources through research in books, journals, and articles. The result of this study is that dispute resolution in franchise agreements or franchises can be judicial or non-judicial. However, many companies have opted for the non-judicial route - arbitration or alternative settlements. Keywords: Franchise, Franchisor, Franchise Agreement, Abitration